2003
DOI: 10.1152/jn.00245.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Effects of Microstimulation in Rat Neocortex: A Parametric Study Using Multielectrode Recordings

Abstract: Butovas, Sergejus and Cornelius Schwarz. Spatiotemporal effects of microstimulation in rat neocortex: a parametric study using multielectrode recordings. J Neurophysiol 90: 3024 -3039, 2003. First published July 23, 2003 10.1152/jn.00245.2003. Using microstimulation to imprint meaningful activity patterns into intrinsically highly interconnected neuronal substrates is hampered by activation of fibers of passage leading to a spatiotemporal "blur" of activity. The focus of the present study was to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
227
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(268 citation statements)
references
References 83 publications
35
227
5
1
Order By: Relevance
“…Orthodromic effects occur either by the direct or by transsynaptic activation of projection neurons with cell bodies in the area that is stimulated. At the current levels used by us, most neurons are stimulated transsynaptically (68). Accordingly, previous studies demonstrated that orthodromic stimulation effects are many times stronger than antidromic effects even between areas with strong direct projections (62,70,71).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Orthodromic effects occur either by the direct or by transsynaptic activation of projection neurons with cell bodies in the area that is stimulated. At the current levels used by us, most neurons are stimulated transsynaptically (68). Accordingly, previous studies demonstrated that orthodromic stimulation effects are many times stronger than antidromic effects even between areas with strong direct projections (62,70,71).…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, our electrical microstimulation experiments provide the first causal evidence that feedforward processing induces γ-oscillations in a higher visual area and that feedback causes α-activity in a lower area. We used electrode arrays for microstimulation, positioned 1 or 1.5 mm below the cortical surface; they were presumably in layers 4 or 5, but the effects of microstimulation on neuronal activity are relatively homogeneous across cortical depth (67,68). Microstimulation activates axons in the vicinity of the electrode tip (68,69) and can cause orthodromic and antidromic stimulation effects in another area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation trains consisted of 10-20 µA biphasic current pulses of 300 µs duration at a rate of 200 Hz. These levels are thought to directly activate neurons within an approximately 100 µm radius of the electrode tip 46 , but indirect activation of neural elements may increase this spread 47 . We applied microstimulation during the entire duration of the motion stimulus on a randomly chosen half of the trials.…”
Section: Electrophysiologymentioning
confidence: 99%
“…However, advanced neuroscience capable of studying cellular interactions in complex networks can be accelerated with selective activation or silencing of neurons of specific types. This feat cannot be achieved easily by electrical stimulation due to its lack of spatial resolution, non-specific stimulation, and the inability to silence neurons 148 .…”
Section: Stimulating Brain Activity Introduction To Optogeneticsmentioning
confidence: 99%